DECISION UNDER RISK CONDITIONS: ADVANTAGES OF TECHNICAL ANALYSIS FOR ARABIC COFFEE FUTURE CONTRACTS IN BM&FBOVESPA - Seii, Cristiano Hayakawa; Lírio, Viviani Silva; Coronel, Daniel Arruda (RC&C: Revista de Contabilidade e Controladoria, 2013)